Physical activity and survival of colorectal cancer patients: population‐based study from Germany - Walter, Viola; Jansen, Lina; Knebel, Phillip; Chang-Claude, Jenny; Hoffmeister, Michael; Brenner, Hermann (International journal of cancer, 2017)
Increasing evidence shows physical activity to be associated with improved colorectal cancer (CRC) prognosis. However, large‐scale prospective patient cohorts, comprehensively ascertaining physical activity,...